Application of virtual reality in a learning experience - Obrist Bertrand, Víctor Udo (2015)
The project is an application that allows users to interact in a virtual environment via a web interface, in which models are in three dimensions to simulate different activities. The application focuses on education with virtual reality technology, enriching the student's perception through the interaction with objects in an artificial world, facilitating their learning. A website was designed for this purpose, on which the application can be executed directly in the web browser with the help of a plugin or downloaded and run as a native application. The user navigates in the virtual environment containing a three-dimensional replica of one of the laboratories of the Polytechnic School UNE. The tests consisted of running the model and laboratory simulations. The results obtained from forms show that the use of virtual reality is valid, accepted and helps understanding the context of the simulations.